Cyberbullying Terhadap Perilaku Penonton Konten Tiktok Gaming ‘’OFFICIAL SIR KEJUU’’ - Nadya Nurfauziyah; Een Irianti; Riza Gusti Rahayu (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This research examines the impact of cyberbullying on viewer behavior on the TikTok platform, especially on the gaming account "Official Sir Cheese." With the rapid growth of social media and the popularity of gaming content, the phenomenon of cyberbullying has become an increasingly pressing issue. This research aims to analyze how cyber attacks affect audience interactions and behavior following gaming content from "Official Sir Cheese." The research method involved qualitative analysis of comments and messages received by the account, as well as interviews with viewers who experienced the direct impact. The research results show that cyberbullying can result in significant changes in audience behavior, including decreased active participation, increased anxiety, and changes in the way they interact with online content and communities. This research suggests the need for mitigation strategies to protect audiences from the negative impacts of cyberbullying and maintain a healthy and supportive online environment.